2017
DOI: 10.1002/mp.12346
|View full text |Cite
|
Sign up to set email alerts
|

Transmission characteristics of a two dimensional antiscatter grid prototype for CBCT

Abstract: Aim High fraction of scattered radiation in cone-beam CT (CBCT) imaging degrades CT number accuracy and visualization of low contrast objects. To suppress scatter in CBCT projections, we developed a focused, two-dimensional antiscatter grid (2DASG) prototype. In this work, we report on the primary and scatter transmission characteristics of the 2DASG prototype aimed for linac mounted, offset detector geometry CBCT systems in radiation therapy, and compared its performance to a conventional one-dimensional ASG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 53 publications
(148 reference statements)
1
64
0
Order By: Relevance
“…CNR improvements between 8% and 52% are achieved with the 2‐D ASG over 1‐D ASG results. Our previous studies suggested that the improvement in CNR is due to both higher primary transmission and lower scatter transmission . Other published studies indicated that, CNR may even be degraded by 1‐D ASG in low‐scatter imaging conditions due to lower primary transmission of 1‐D ASG …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…CNR improvements between 8% and 52% are achieved with the 2‐D ASG over 1‐D ASG results. Our previous studies suggested that the improvement in CNR is due to both higher primary transmission and lower scatter transmission . Other published studies indicated that, CNR may even be degraded by 1‐D ASG in low‐scatter imaging conditions due to lower primary transmission of 1‐D ASG …”
Section: Discussionmentioning
confidence: 87%
“…We demonstrated an improvement in primary transmission characteristics in projections acquired with the 2D‐ASG compared with projections acquired with 1D‐ASG. With respect to 1D‐ASG, projections acquired with 2D‐ASG displayed a factor of 3–6 lower scatter to primary ratio, and a factor of 1.3–1.4 improvement in CNR . In this letter, we present the first CBCT images produced from projections acquired using the 2D‐ASG prototype, and report on the improvement in CT number accuracy, reduction of image artifacts, and improvement in CNR.…”
Section: Introductionmentioning
confidence: 99%
“…However, controversial results are also found in the literature using other animal models where the evaluation of peri‐implant bone defect regeneration by means of CBCT was not accurate for sites providing bone width of <0.5 mm 39 . Research to reduce artifacts caused by titanium implants in CBCT images is emerging 45,48 …”
Section: Resultsmentioning
confidence: 99%
“…39 Research to reduce artifacts caused by titanium implants in CBCT images is emerging. 45,48 Kühl et al 42 reported high sensitivity of the CBCT scans when evaluating 1-and 3-mm defects. However, the specificity of CBCT is lower than that found when intraoral periapical radiographs are used.…”
Section: Use Of Cbct For Diagnosis and Treatment Outcome Assessmentmentioning
confidence: 99%
“…To address this problem, two‐dimensional antiscatter grids (2DASG), a 2D array of through‐holes separated by tungsten septa, have been investigated recently. With respect to conventional ASGs, we have shown that 2DASG provides substantially better scatter rejection and primary x‐ray transmission performance, and therefore, has the potential to further improve CBCT image quality …”
Section: Introductionmentioning
confidence: 99%